2013
DOI: 10.1371/journal.pone.0063653
|View full text |Cite
|
Sign up to set email alerts
|

CBARA1 Plays a Role in Stemness and Proliferation of Human Embryonic Stem Cells

Abstract: Human embryonic stem cells (hESCs) are capable of unlimited self-renewal and can generate almost all of the cells in the body. Although some pluripotency factors have been identified, much remains unclear regarding the molecules and mechanisms that regulate hESC self-renewal and pluripotency. In this study, we identified a mitochondrial gene, CBARA1, that is expressed in undifferentiated hESCs and that is down-regulated rapidly after cellular differentiation. To study its role in hESCs, endogenous CBARA1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…noX5 may be able to reduce oxidative stress and may be associated with calcium ion channel-related oxidative stress in lymph nodes (44). WWP2 also exhibits protein binding and ligase activities (28); it is involved in the ubiquitination process, circulation and viral entry into host cells (28). WWP2 has a negative regulatory effect on Toll-like receptor 3-mediated innate immunity (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…noX5 may be able to reduce oxidative stress and may be associated with calcium ion channel-related oxidative stress in lymph nodes (44). WWP2 also exhibits protein binding and ligase activities (28); it is involved in the ubiquitination process, circulation and viral entry into host cells (28). WWP2 has a negative regulatory effect on Toll-like receptor 3-mediated innate immunity (45).…”
Section: Discussionmentioning
confidence: 99%
“…Based on P-values and the functions of related genes according to GenBank (https://www.ncbi.nlm.nih.gov/; accessed on February 18, 2018), four genes were ultimately selected for verification (Table VI). WWP2 is an e3 ubiquitin protein ligase containing a WW domain that participates in the ubiquitination process and viral entry into host cells (28). AKT2 has shown nucleotide binding, protein serine, threonine kinase, protein binding, aTP-binding and transferase activities, and participates in protein amino acid phosphorylation and diabetes development (29).…”
Section: Leukocytosis Vs Normal Controlmentioning
confidence: 99%
“…15,16 Antony et al found that on liver-specific MICU1 loss, partial hepatectomy resulted in lethargic mice. Furthermore, the pro-inflammatory phase does not resolve in such mice and liver regeneration fails, with evidence of impaired cell cycle entry and extensive necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…MICU1 (Gene ID: 10367) could encode an essential regulator of mitochondrial Ca 2+ uptake under basal conditions. The encoded protein interacts with the mitochondrial calcium uniporter and is essential in preventing mitochondrial Ca 2+ overload that could cause excessive production of reactive oxygen species and cell stress (Mallilankaraman et al, 2012;Arvizo et al, 2013;Chen et al, 2013;Hoffman et al, 2013;Logan et al, 2014). OIT3 didn't obtain any annotated results from Gene database, but get some other annotated messages from GO, INTERPRO, PFAM, SMART annotation analysis provided by DAVID (Table 2).…”
Section: Gene Annotationmentioning
confidence: 99%